Design, synthesis and antifungal activity of threoninamide carbamate derivatives via pharmacophore model. (1st January 2020) - Du, Xiu-Jiang; Peng, Xing-Jie; Zhao, Rui-Qi; Zhao, Wei-Guang; Dong, Wei-Li; Liu, Xing-Hai
Abstract: Thirty-six novel threoninamide carbamate derivatives were designed and synthesised using active fragment-based pharmacophore model. Antifungal activities of these compounds were tested against Oomycete fungi Phytophthora capsici in vitro and in vivo. Interestingly, compound I-1, I-2, I-3, I-6 and I-7 exhibited moderate control effect (>50%) against Pseudoperonospora cubensis in greenhouse at 6.25 μg/mL, which is better than that of control. Meanwhile most of these compounds exhibited significant inhibitory against P. capsici . The other nine fungi were also tested. More importantly, some compounds exhibited remarkably high activities against Sclerotinia sclerotiorum, P. piricola and R. solan in vitro with EC50 values of 3.74–9.76 μg/mL. It is possible that the model is reliabile and this method can be used to discover lead compounds for the development of fungicides.